Associations of increased spatial QRS-T angle with cardiovascular risk factors: data from the regional sample of ESSE-RF study - G. A. Muromtseva; E. A.-I. Aidu; Yu. K. Makarova; V. A. Kutsenko; E. B. Yarovaya; V. G. Trunov; Yu. A. Balanova; A. V. Kapustina; S. E. Evstifeeva; A. Yu. Efanov; S. A. Shalnova; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2021)
Aim. To study the associations of increased spatial QRS-T angle (sQRS-Ta ≥90°) with cardiovascular risk factors (RFs).Material and methods. We analyzed 1411 electrocardiography (ECG) records of men and women aged 25-64 years from a random regional sample of the Epidemiology of Cardiovascular Diseases and their Risk Factors in Regions of Russian Federation (ESSE-RF) study. Relationships of sQRS-Ta with the following RFs were assessed: hypertension (HTN), systolic blood pressure (SBP) ≥140 mm Hg, diastolic BP (DBP) ≥90 mm Hg, pulse pressure (PP) ≥60 mm Hg; glucose ≥7,0 mmol/l, hypercholesterolemia; hypertriglyceridemia; high-density lipoprotein cholesterol (HDL-C) ≤1,0/1,2 mmol/l in men/women, low-density lipoprotein cholesterol (LDL-C) >3,0 mmol/l; C-reactive protein (CRP) >1 mg/L; overweight, obesity and abdominal obesity; heart rate (HR) >80 bpm; age >52 years.Results. Weak but significant correlations of sQRS-Ta with age (in women), SBP, DBP, PP, body mass index, waist circumference, lipids, glucose, CRP were revealed. Univariate logistic regression demonstrated significant associations of increased sQRS-Ta with HTN, elevated SBP and PP, overweight, obesity and abdominal obesity, hypercholesterolemia, elevated LDL-C and CRP, hyperglycemia, age >52 years and heart rate >80 bpm. There were no associations of increased sQRS-Ta with male sex, elevated DBP, smoking, hypertriglyceridemia, and low HDL-C levels. The sQRS-Ta associations characteristic of women was similar with associations found among the entire sample. Men with increased sQRS-Ta had no associations with any of analyzed RFs. In multivariate models, increased sQRS-Ta was associated with the following combination of RFs: age >52 years, heart rate >80 bpm, HTN, increased PP, overwaight, and male sex. According to direct stepwise selection among all subjects and in women, the main contribution to sQRS-Ta was made by SBP, age, HDL-C and heart rate.Conclusion. Despite the significance of stepwise regression model (p=0,0001), the low coefficient of determination R2 may indicate other not yet identified determinants with relevant associations with sQRS-Ta.